MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN ISI TEKS BACAAN MELALUI PENDEKATAN WHOLE LANGUAGE PADA SISWA KELAS IV SD NEGERI 6 BONTOKAMASE KECAMATAN SOMBA OPU KABUPATEN GOWA (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The aims of the study were to improve: 1) the learning process of reading comprehension using the whole language approach, and 2) the ability to read comprehension through the whole language approach in fourth grade students at SD Negeri 6 Bontokamase, Gowa The type of research used in this research is collaborative Classroom Action Research. The subjects of this study were 35 grade IV students at SD Negeri 6 Bontokamase, Gowa. The research design used is the Kemmis and Mc.Taggart model. The data collection methods used in this study were: 1) tests, 2) observations, 3) documentation, and 4) field notes. Data analysis techniques were carried out in a quantitative and qualitative descriptive manner.The results of the study show that learning to read comprehension through the whole language approach can increase student activity and attention. Seen from the involvement of students in various learning activities.Learning to read comprehension uses a whole language approach improve students' KKM. The results of tests, observations, documentation, and field notes show that through a whole language approach can improve reading comprehension skills in fourth grade students of SD Negeri 6 Bontokamase, Gowa. The increase in reading comprehension skills in the first cycle was 8.18, the initial conditions increased from 62.28 to 70.46.